Leveling osteotomy of the tibial plateau at an inverted angle in a dog - Bernardi, Paula Eduarda Quintana (2022)
One dog, Golden Retriever, 5 months old, was seen complaining of lameness and pain in the left pelvic limb. Avulsion of the tibial crest was diagnosed by radiographic means, which was corrected with a tension band. The absence of postoperative radiographic monitoring and the non-removal of the apparatus led to the early closure of the cranial tibial physis with continuous flow growth, resulting in pain, functional loss of the limb after one year and at a 13.2ºtibial plateau angle negative. The biomechanical alteration of the limb was corrected using the inverted TPLO technique, converting the angle of the tibial plateau to 5.3 positive, without a rockback evidenced in 30, 60, 90 days up to four months after the operation. The objective of this case report is to describe the surgical correction with the inverted TPLO technique in a case of angle of the negative tibial plateau secondary to not removing the tension band applied in avulsion of the growing tibial crest. After 120 days, the dog was presented fully recovery and weight-bearing without any complication.